PENGUJIAN DAN PERAWATAN MESIN GRANULAR - Zul Ihsan; Robby Gunawan; Eka Sunitra; Rivanol Chadry; Yuli Yetri (Jurnal Energi dan Teknologi Manufaktur, 2020)
This paper discusses the granulator machine testing process. This test aims to determine the process of occurrence of granular. Granular pellets are one form of feed pellets, granular (rounded) and light in weight. Granular pellets are not easy to sink but are easily broken down in water. This type of pellet is made without going through the process of pressing, so that it can produce feed grains that are light weighted, not easily submerged but easily decomposed in water. The goal is to determine the optimal state of the granulator machine with three angular tilt positions, it can perform maintenance on the granulator machine. The granulator machine testing process is carried out by means of the plate angle measurement process, the water mixture measurement process, the plate speed measurement process. Material used for the testing process uses flour and water. While the tools used in the granulator machine testing process are spray, 14 key, sieve, and container. After testing at 3 angles at an angle of 25o, angle of 30o and angle of 35o the authors conclude that this machine can produce small granules at a slope of 250 with an engine speed of 17 rpm and average weight of granular which is produced 236 grams. While the results of hourly 3 kg / hour.